Endovascular embolization in temporo-occipital intraparenchymatous hemorrhage due to arteriovenous fistula. Case report - Palacios, Angely (2023)
Cerebral arteriovenous malformations are an infrequent pathology, of which fistulous malformations are the least common. Surgical clinical management is not fully defined, so analyzing the efficacy of embolization in these patients is an important scientific contribution to society. A 28-year-old male patient with headache of 10/10 on the visual analog pain scale. Imaging studies were performed and showed intraparenchymal hemorrhage; computed tomography angiography revealed a ruptured cerebral arteriovenous malformation in the temporo-occipital region dependent on the middle cerebral artery; complex endovascular embolization was performed, with favorable results in his evolution. In conclusion, embolization as a treatment for hemorrhagic temporo-occipital arteriovenous malformation is a viable alternative in patients with stage IV on the Spetzler scale.